2009
DOI: 10.1161/atvbaha.109.192583
|View full text |Cite
|
Sign up to set email alerts
|

Interplay Between Human Adipocytes and T Lymphocytes in Obesity

Abstract: Objective-Adipose tissue (AT) plays a major role in the low-grade inflammatory state associated with obesity. The aim of the present study was to characterize the human AT lymphocytes (ATLs) and to analyze their interactions with adipocytes. Methods and Results-Human ATL subsets were characterized by flow cytometry in subcutaneous ATs from 92 individuals with body mass index (BMI) ranging from 19 to 43 kg/m 2 and in paired biopsies of subcutaneous and visceral AT from 45 class II/III obese patients. CD3ϩ ATLs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
116
1
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 203 publications
(135 citation statements)
references
References 23 publications
15
116
1
3
Order By: Relevance
“…We and others have previously shown that a significant percentage of CD4 + T cells in adipose tissue have a memory Th1 phenotype [3,8]. In this study, we further investigate this T-cell population and show that there is an enrichment of IFN-γ-secreting cells in adipose tissue compared with peripheral blood from the same individuals.…”
Section: Introductionmentioning
confidence: 57%
See 3 more Smart Citations
“…We and others have previously shown that a significant percentage of CD4 + T cells in adipose tissue have a memory Th1 phenotype [3,8]. In this study, we further investigate this T-cell population and show that there is an enrichment of IFN-γ-secreting cells in adipose tissue compared with peripheral blood from the same individuals.…”
Section: Introductionmentioning
confidence: 57%
“…Moreover, some adipocytederived soluble mediators, such as leptin [10, have been shown to modulate differentiation or cytokine production by CD4 + T cells. However, adipocytes can release a large number of soluble mediators with different biological functions and their global effect on T cells is unknown.We and others have previously shown that a significant percentage of CD4 + T cells in adipose tissue have a memory Th1 phenotype [3,8]. In this study, we further investigate this T-cell population and show that there is an enrichment of IFN-γ-secreting cells in adipose tissue compared with peripheral blood from the same individuals.…”
mentioning
confidence: 57%
See 2 more Smart Citations
“…L'importance physiopathologique de ces changements est illustrée par le fait que l'inactivation des T CD8 + [13] ou l'induction des lymphocytes Th2 ou des Treg [14,15] diminue l'inflammation dans le tissu adipeux des souris DIO. Chez l'homme, une étude montre l'augmentation des lymphocytes T CD8 + et lymphocytes CD4 + avec le degré d'adiposité dans le tissu adipeux [16]. L'ensemble de ces observations suggèrent l'existence d'un jeu complexe d'influence entre les différents acteurs cellulaires de l'immunité innée (neutrophiles, mastocytes), adaptative (lymphocytes) ou à l'interface des deux systèmes (NKT).…”
Section: Pourquoi Le Tissu Adipeux Est-il Enflammé ?unclassified